Štiridesetletnica organiziranega entomofavnističnega delovanja v severovzhodni Sloveniji - Devetak, Dušan (Acta entomologica slovenica (Ljubljana), 2022)
Prior to 1982, there was no organized activity of entomologists in northeastern Slovenia. Before the Second World War, in northeastern Slovenia - in addition to a large number of German-speaking entomologists - only a handful of Slovenes collected insects from this area. the year of birth of today's Slovenian entomological Society "Štefan Michieli" is 1952, when the entomology Group at the natural History Society of Slovenia was established. The milestone in the work of entomologists of northeastern Slovenia was the year 1982, which we have for the beginning of their organized work. At that time, entomologists from Štajerska, Koroška and Prekmurje met formally for the first time. In 2022, Slovenian entomologists are celebrating several anniversaries - the 70th anniversary of the founding and operation of the Slovenian entomological Society "Štefan Michieli", the 40th anniversary of the organized work of the entomologists of northeastern Slovenia and the 30th anniversary of the founding and operation of the Slovenian odonatological Society. In this contribution, a brief review of the history of these activities in northeastern Slovenia is presented.
Keywords: favnistika; severovzhodna Slovenija; zgodovina entomologije